Cross-lagged analysis of mobile phone addiction and bedtime procrastination: a comparison of gender and perceived stress levels among Chinese college students - Lin, Xiujian; Fu, Xueping; Shen, Yuhao; Liu, Gaoyang; Ding, Ningning; Zhang, Guohua; Qian, Jun (Frontiers in Psychology, 2025)
PurposeThis study aims to investigate the longitudinal relationship between Mobile Phone Addiction (MPA) and Bedtime Procrastination (BP) and to analyze differences across various gender and stress level groups, providing a theoretical basis and practical guidance for the development of relevant intervention strategies.MethodsA longitudinal research design was employed, conducting two surveys among 1,423 first-year to junior college students at a university in Wenzhou, Zhejiang Province, in November 2021 and May 2022. Measurements were taken using the Mobile Phone Addiction Scale, Bedtime Procrastination Scale, and Depression Anxiety Stress Scale-21 (DASS-21). Data were analyzed using SPSS 26.0 and AMOS 24.0, employing methods such as descriptive statistics, correlation analysis, repeated measures variance analysis, and structural equation modeling.ResultsThe study found that both MPA and BP are on the rise among college students and share a bidirectional longitudinal relationship. Under low-stress conditions, MPA significantly predicted subsequent BP, while under high-stress, BP significantly predicted subsequent MPA. Additionally, gender-specific analyses revealed that MPA significantly predicted subsequent BP in both male and female students, but BP only significantly predicted subsequent MPA in female students.ConclusionMPA and BP mutually influence each other among college students, with this relationship being moderated by stress levels and gender. Personalized intervention measures should be adopted for college students of different genders and stress levels to effectively prevent and alleviate MPA and BP, promoting the healthy growth and comprehensive development of college students.